Stable Isotope Dating of Historic Buildings. (1st January 2019) - Miles, D.; Loader, N. J.; Young, G. H. F.; McCarroll, D.; Davies, D.; Ramsey, C. Bronk; James, J. G.
Abstract : The recent development of an oxygen isotope (δ 18 O) master chronology for south central England (1200–2000 AD) has successfully demonstrated reliable cross-dating between the master chronology and undated samples from vernacular and high-status buildings. The method is well suited to complacent, wide-ringed samples, which are commonplace throughout the UK historic buildings archive and often fail to date by ring-width dendrochronology, or remain unsampled. This paper outlines briefly the isotope dating technique, and describes the application of the method to a number of case studies where ring-width dendrochronology has been unable to provide a robust date. The close association between ring-width dating and stable isotope dendrochronology is explored and its wider potential considered. Note: For illustrations of the buildings used in the case studies, see "Stable Isotope Tree-ring Dates: List 1, " Vernacular Architecture 50: 88–93 .